Ontology-based Development of the Metamodels for Modelling Distributed Parallel Software Systems - Malakhov, Eugene; Mezhuyev, Vitaliy (2015)
The paper proposes the method for the development of metamodels for the modelling distributed parallel software systems. The method is an important stage of Domain-Specific Mathematical Modelling (DSMM), developed to enhance the methodology of Domain-Specific Modelling. The advantage of DSMM is a possibility of constructing metamodels for the modelling domains, having different mathematical properties and structures. The paper analyses applicability of OWL-DL ontologies for expressing properties of software systems. Identification of the metatypes as OWL classes and use of OWL restrictions as metamodels’ grammars give us an effective way for the design and verification of software systems. The proposed approach have advantages of the model driven software development and allows verification of software systems at earlier design stage.